Amphibians & reptiles of the Carolinas and Virginia - Beane, Jeffrey C.; ebrary, Inc. (Chapel Hill : University of North Carolina Press, 2010)
Revised and updated to reflect the most current science, and including 30 new species, this authoritative and comprehensive volume is the definitive guide to the amphibians and reptiles of the Carolinas and Virginia. The new edition features 189 species of salamanders, frogs, crocodilians, turtles, lizards, and snakes, with updated color photographs, descriptions, and distribution maps for each species. It is an indispensable guide for zoologists, amateur naturalists, environmentalists, backpackers, campers, hikers, and everyone interested in the outdoors.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Amphibians -- North Carolina -- Identification; Amphibians -- South Carolina -- Identification; Amphibians -- Virginia -- Identification; Reptiles -- North Carolina -- Identification; Reptiles -- South Carolina -- Identification; Reptiles -- Virginia -- Identification; Electronic books